Penggunaan Media Sosial Tik Tok, Dompet Digital, Dan Literasi Keuangan Syariah Terhadap Perilaku Konsumtif Berbelanja Online Pada Generasi Z Di Kota Banjarmasin - Aulia Rahmi; Erissa Nilasari; Abdul Gafur (Al-Ujrah | Jurnal Ekonomi Syariah, 2024)
TikTok social media is thought to influence the consumer behavior of Generation Z, who are quick to apply technology on a daily basis. The existence of restrictions and prohibitions on the use of TikTokShop shows that TikTok, especially TikTokShop, can influence consumer behavior patterns. The high use of the internet makes it easier to use digital wallets with flexibility. It is hoped that sharia financial literacy can reduce the consumptive behavior of Gen Z. This research aims to determine the simultaneous and partial influence of independent variables on the dependent variable. This type of research is field research. This research uses a quantitative approach. And the sampling technique uses incidental sampling and calculates the sample using the Lemeshow formula because the population size cannot be known with certainty. The data collection technique was carried out using a questionnaire. Data analysis techniques consist of research instrument tests which include validity and reliability tests, classical assumption tests which include normality, multicollinearity and heteroscedasticity tests, multiple linear regression analysis, coefficient of determination, and hypothesis tests which include the F test and T test. Simultaneously, it shows that the influence of the independent variable on the dependent variable is 31.3% and 68.7% is influenced by variables outside the research. The results of the T test (partial) show that the social media variables TikTok and sharia financial literacy have a positive effect as evidenced by the significance values, namely 0.00 and 0.02 < 0.05, which means that Ho is rejected and Ha is accepted. And for the digital wallet variable with a significant value of 0.12 > 0.05, which means there is no positive influence on consumer behavior (Y), then Ho is accepted and Ha is rejected.